Influence of Students’ Personal Qualities on Understanding Lies as a Psychological Phenomenon - Mayorchak, Natalia (Psychological Prospects Journal, 2015)
The results of the theoretical study of lies and deceit phenomenon, their types and methods of determination and the results of empirical research aimed at studying subjective perceptions of students about the lies and deception, the relationship between beliefs and personal characteristics of the subjects are presented in the article. Lies, deception and falsehood are part of social and psychological life of man. Researchers of natural prerequisites of mind rightly emphasize the role of hereditary and biological factors that determine the development of the individual, in turn, are becoming less favorable because of environmental degradation and natural human environment. Cheating – a half-truth that provokes someone who sees it, the false conclusions from true facts; reporting some real facts, deliberately hides other trickster, important for understanding information. Since ancient times military trick is used, based generally on deception. In our research we assume that the individual psychological characteristics of students affect the characteristics of their ideas about the lies and reflect their constituent stereotypes of reasons, the prevalence, frequency and appropriateness of its use in social contacts. We assume that differences in the nature and direction of lie use are reflected in the individual behavior strategies. The characteristics of respondents who have an idea of cheating as a way to achieve their goals are the display of a high level of approval motivation, domination, insight and inclination to projection as a protective mechanism. Subjects who resort to lies constantly inherent lower self-esteem, but at the same time – the desire for power and domination, they tend not to take other’s advice and are intolerant of criticism. People who use lies rarely inherent such qualities as confidence, independence and realism in judgments and actions, domination intuitive channel of empathy that allows the respondent to see the behavior of partners to act in a shortage of baseline information about them, drawing on the experience stored in the subconscious. For those who consider the possibility of noble lies and use of inherent features such as the dominance of identification (ability to understand the other based on empathy, setting yourself on partner’s place), low self-esteem of approval motivation. The category of subjects that does not separate the lies inherent focus on personal (self-interest), which is associated with prevalence of their own well-being motives. People who use lies situationally, due to certain circumstances have low self-esteem of approval motivation, marginal orientation, resulting in the propensity to obey circumstances and impulsive behavior.
Keywords: students, lies, deception, subjective ideas, personality features.